Weather conditions of military operations. The influence of atmospheric conditions on the course of pitch battles and military campaigns in the Middle Ages. Selected examples - Niewiński, Andrzej (Armia kontra natura, 2020)
The article examines the impact of adverse weather conditions and astronomical occurrences on the outcome of the selected medieval military campaigns and pitch battles. Unpredictability of weather was an important factor in medieval warfare: unexpected wind, rain, snow, heat or day-to-night temperature fluctuations could influence a military operation in a significant way. As medieval chronicles recorded, troops often suffered from famine as a result of excessive rains, droughts or adverse winds which prevented supplies from being delivered by sea. Apart from causing fatigue and exhaustion bad weather contributed to disease outbreaks and equipment damage. People were weakened physically and psychologically which reduced their fighting ability.